Biomedical Research at the Time of "Publish or Perish". Issue 4 (October 2015) - Quintaliani, Giuseppe; Nicoletti, Ildo
"Publish or Perish" describes the pressure exerted on scientific researchers to continually and rapidly publish, to demonstrate academic talent, to obtain financial support for their research, and to progress in their career. The pressure to publish seems to be one of the main causes of the reduction in the quality of scientific work submitted for publication, and in some cases leads to scientific misconduct and fraud. The number of articles retracted for fraud has sharply increased in the last years, indicating a crisis of the "peer-review" system, producing a waste of financial resources, mining the reliability of researchers and in some cases posing risks for human health. Although the solution of this problem lies on the full recovery of "research ethics", institutions should apply strict oversight to ensure research integrity. Furthermore, funders and research agencies must support and reward researchers who do solid science and hold to account those whose methods are questionable.